2006
DOI: 10.1158/1078-0432.ccr-06-0547
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Pathway Profiling and Microsatellite Instability in Colorectal Cancer

Abstract: Background: The ability to maintain DNA integrity is a critical cellular function. DNA repair is conducted by distinct pathways of genes, many of which are thought to be altered in colorectal cancer. However, there has been little characterization of these pathways in colorectal cancer. Method: By using theTaqMan real-time quantitative PCR, RNA expression profiling of 20 DNA repair pathway genes was done in matched tumor and normal tissues from 52 patients with Dukes' C colorectal cancer. Results: The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…Aberrant promoter methylation of BER and NER genes have already been reported in other types of cancer, but not studied in CRC (15). An investigation of expression profiles of some BER and NER genes in tumor tissue did provide preliminary characterizations (16). Previous studies carried out on peripheral blood mononuclear cells (PBMC) showed suppressed BER and NER capacities in patients with CRC compared with healthy individuals (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant promoter methylation of BER and NER genes have already been reported in other types of cancer, but not studied in CRC (15). An investigation of expression profiles of some BER and NER genes in tumor tissue did provide preliminary characterizations (16). Previous studies carried out on peripheral blood mononuclear cells (PBMC) showed suppressed BER and NER capacities in patients with CRC compared with healthy individuals (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation on transcription-coupled repair has mainly focused on the mutations in Cockayne syndromes (11). SNPs in the CSB gene have been reported to affect cell survival (11) and to be associated with cancer risk (12,13). For example, the CSB Met1097-Val polymorphism had a significant impact on recurrence of superficial bladder cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…Regions conserved between species are likely to contain functionally important domains. Recently, one colorectal cancer study observed that XRCC1 RNA expression was correlated with microsatellite instability status among Caucasian Americans (Yu et al 2006); one study of familial breast cancer showed that XRCC1 IVS10 + 141G?A was associated with increased expression of XRCC1 mRNA and protein among Caucasian Americans (Bu et al 2006); and one bladder cancer study reported that XRCC1 proteins were strongly associated with patient outcome following radiotherapy among Caucasian British (Sak et al 2005). Those results suggested that XRCC1 plays an important functional role in cancer development and prognosis, although the underlying molecular mechanisms of XRCC1 Pro206Pro and Gln632Gln remain to be established.…”
Section: Discussionmentioning
confidence: 99%